2020
DOI: 10.1038/s41467-020-20068-5
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of ε-iron carbide as high-temperature catalyst under realistic Fischer–Tropsch synthesis conditions

Abstract: The development of efficient catalysts for Fischer–Tropsch (FT) synthesis, a core reaction in the utilization of non-petroleum carbon resources to supply energy and chemicals, has attracted much recent attention. ε-Iron carbide (ε-Fe2C) was proposed as the most active iron phase for FT synthesis, but this phase is generally unstable under realistic FT reaction conditions (> 523 K). Here, we succeed in stabilizing pure-phase ε-Fe2C nanocrystals by confining them into graphene layers and obtain an iron-time y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 49 publications
2
86
0
Order By: Relevance
“…36-1249) emerged. The HRTEM image and the corresponding FFT pattern of spent Fe 4 /C bio (Figure S5) also proved that the measured lattice spacings of 0.21 nm corresponded to the (101) planes of ε-Fe 2 C. Recent works (Lyu et al, 2020b;Xu et al, 2014) had shown that ε-Fe 2 C was a more active phase than c-Fe 5 C 2 in FTS and this was another significant reason for the high performance of biosugarcane-based Fe c /C bio catalysts. And the formation of ε-Fe 2 C was not a coincidence.…”
Section: Key Reasons For the Performance Of Biosugarcane-based Fe/c Bio Catalystsmentioning
confidence: 64%
“…36-1249) emerged. The HRTEM image and the corresponding FFT pattern of spent Fe 4 /C bio (Figure S5) also proved that the measured lattice spacings of 0.21 nm corresponded to the (101) planes of ε-Fe 2 C. Recent works (Lyu et al, 2020b;Xu et al, 2014) had shown that ε-Fe 2 C was a more active phase than c-Fe 5 C 2 in FTS and this was another significant reason for the high performance of biosugarcane-based Fe c /C bio catalysts. And the formation of ε-Fe 2 C was not a coincidence.…”
Section: Key Reasons For the Performance Of Biosugarcane-based Fe/c Bio Catalystsmentioning
confidence: 64%
“…As for the CO-TPD profile of activated CuFeO 2 , two peaks at 290 and 501 °C appeared, corresponding to non-dissociative and dissociative adsorption of CO, respectively (Fig. 4a ) 34 , 37 . The non-dissociative adsorption of CO* was further supported by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) measurements using CO as a probe molecule.…”
Section: Resultsmentioning
confidence: 98%
“…The CO-TPD profile of activated Fe 2 O 3 shows a peak at 508 °C for dissociative adsorption of CO (Fig. 4a ) 34 . Considering that activated Fe 2 O 3 comprised Fe 3 O 4 and χ-Fe 5 C 2 , we proposed the reaction scheme of activated Fe 2 O 3 as that for Fe-based catalysts previously reported 16 , 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…[207] Lyu et al recently succeeded in stabilizing an ε-Fe 2 C phase, which was considered as the most active but not stable phase under typical FT reaction conditions, inside graphene layers by a pyrolysis method. [208] The obtained ε-Fe 2 C@graphene catalyst exhibited an ultrahigh activity (1258 μmol CO g Fe −1 s −1 ) in FT synthesis, and meanwhile, the catalyst exhibited excellent stability in 400 h reaction. In addition to the activity and stability, the product selectivity could be tuned by the confinement effect.…”
Section: Confinement By Shaped Carbonsmentioning
confidence: 87%